Promoting Mental Health among Postpartum Mothers through Mindfulness Practice in Tuban Regency - Ilmiatus Qoyimah; Nurus Safaah (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2025)
Postpartum mothers often experience psychological challenges such as stress, anxiety, and feelings of inadequacy, which may be intensified by the pervasive influence of social media. This community service program aimed to enhance the mental health of postpartum mothers in Tuban Regency through the application of mindfulness practices. The program employed a participatory approach involving posyandu cadres and village midwives, with a purposive sample of 30 postpartum mothers attending four weekly mindfulness sessions. Each session consisted of psychoeducation on mental health, guided mindfulness exercises, and group discussions, supported by daily home practice using audio recordings. Monitoring was conducted via a WhatsApp group, and evaluations were carried out using pre- and post-assessments with the DASS-21 instrument and participant feedback surveys. The results showed notable improvement in mental health outcomes: moderate stress decreased from 40% to 15%, mild anxiety from 30% to 10%, and mild depression from 10% to 3%, while normal conditions increased from 20% to 72%. Participants reported greater calmness, self-awareness, and emotional stability. In conclusion, mindfulness practice was found to be an effective and practical approach to improving the mental health of postpartum mothers, with strong potential for integration into community health services.